First occurrence of knight rock shrimp, Sicyonia lancifer (Olivier, 1811) (Decapoda: Sicyoniidae) in the Mediterranean Sea. - PATANIA, A.; MUTLU, E. (Mediterranean Marine Science, 2015)
The occurrence of the non-native species Sicyonia lancifer (Olivier, 1811) belonging to Sicyoniidae family is reported for the first time in the Mediterranean Sea. In the following paper the distinguishing features of the species are provided.